Pengaruh Keterlibatan Karyawan Dalam Proses Rekrutmen Terhadap Keberhasilan Rekrutmen Organisasi - Angela Clarawati; Yolenta Stefani Babaro; Dhea Anada; Yusawinur Barella (Institut Nalanda, 2024)
This research aims to determine the effect of employee involvement in the recruitment and job assignment process on employee performance. The research results also show that employee work performance achievement refers to the employee's abilities. Human resources are a very effective source because they can produce organizational success anywhere, this is also an important part considering the very tight competition. In order to improve performance to perfection, the company must also be able to ensure that an employee is selected and assigned to the right work assignment or position for where they work. This research aims to determine the influence of an employee's recruitment, appointment and commitment to work on employee performance in human resources.